The Fiscal Impact of Foreign Aid In Rwanda : A Theoretical And Empirical Analysis - Ezemenari, Kene (The World Bank, 2008)
The inflow of large quantities of foreign aid into Rwanda since 1994 can have potential adverse effects such as aid dependency via a significant negative effect on tax efforts and on public investments. This paper carries out a theoretical and empirical study to examine these issues. The theoretical part develops a model in which the recipient government decides on the optimal level of tax and optimally allocates total government revenue between current expenditure and public investment. The theoretical model makes it possible to empirically test whether an increase in aid is likely to reduce the optimal tax rate and the proportion of public expenditure allocated to public investment. The econometric analysis uses time series data on Rwanda to show, in line with other studies in the literature, a negative relationship between increased aid and the tax rate; but the magnitude of the effects are extremely small. In the case of Rwanda, reforms to the tax administration and expansion of the tax base have had mitigating effects. As far as the effect on public investment, the overall effect was negative in the past; however, since 1995 the direction of this effect has changed